KAJIAN PENERAPAN SENSOR MIC-CONDENSER DALAM RANCANG BANGUN SOUND LEVEL METER DIGITAL. - Achmad Komarudin; Hariyadi Singgih; Moh. Luqman (JURNAL ELTEK, 2018)
Noise levels in the industrial and urban streets have a threshold value that has been determined by the Regulation of the State Minister of the Environment Number 07 Year 2009 for motor vehicles. And Minister of Manpower Number: KEP-51 / MEN / 1999 for industrial environment. To know the value of noise is required a Digital Level Sound Meter gauge that can be used as a measuring instrument of sound intensity noise value of motor vehicle exhaust and other sound sources. This tool can change the amount of sound pressure converted in LCD display. This Digital Sound Level Meter is used to measure the feasibility of thresholds on exhaust and other sound sources. The purpose of this research is to study the application of Mic-condenser sensors in Digital Sound Level Meter design The research method is to design and design the system, using mic condenser sensor, designing signal conditioner using op-amp with series of Absolute Value Modulus (MAV), which can rectify AC voltage into DC using Microkontroller ATMega 8535 as data processing result of data processing which has become the quantity sound pressure with decibels (dBA) is presented in LCD devices The results of the system test show that this Digital Sound Level Meter can run and can display the sound pressure level captured by the mic condenser sensor, and from the result of the Digital Sound Level Meter test compared to the comparison tool obtained an error of 2.94%.